Technology of Recovering Refractory from Waste of Bauxite Chamotte by Color Separation Technology - Yulin LIU; Changmiao LIU; Tuaner PENG; Jian XU (Kuangchan zonghe liyong)
After the bauxite is fired into the clinker, the bauxite chamotte high in iron content is handpicked out because of the color difference, and the bauxite chamotte high in iron content by handpicked was discarded because it does not meet the requirements of the refractory. This test takes waste of bauxite chamotte as raw materials. Firstly, the raw materials are crushed to 5～10 mm, and then the raw materials are sorted by photoelectric color separator. Finally, qualified refractory raw materials with total iron content less than 2% can be obtained. The total iron grade of concentrate product is 1.48% and the yield is 33.12%. This technology can effectively improve the utilization rate of bauxite in refractory industry, and has a wide application prospect.